The Mick. The complete second season [videorecording (DVD)] - Olson, Kaitlin; Black-D'elia, Sofia; Jiménez, Carla; Barbusca, Thomas (20th Century Fox Home Entertainment, 2018)
Although constantly pulled between enjoying her lavish new lifestyle and trying to control three monstrous children who have unlimited lines of credit, Mickey is now in it for the long haul. With the help of her on-again, off-again boyfriend and the kids' live-in housekeeper, Mickey is determined to make it work, or, at the very least, black out during the parts that don't.